Anti-discrimination Education in Japan: Buraku Sabetsu Simulation - Nojima, Daisuke (In Factis Pax: Journal of Peace Education and Social Justice, 2009)
Here is a sample vignette between a father and a son, in conflict concerning the possible marriage of the son with a woman from the buraku community. The family is faced with a dilemma between love and established custom. Some volunteer performers are asked to read in a skit style, as an introduction of realizing Buraku Sabetsu problem in Japan.